2021
DOI: 10.1177/01445987211002278
|View full text |Cite|
|
Sign up to set email alerts
|

Do renewable energy sources improve clean environmental-economic growth? Empirical investigation from South Asian economies

Abstract: This study investigates the causal relationship between renewable energy sources and clean environmental economic growth among South Asian economies. This study comprises the panel data sets for eight (8) South Asian countries, and data start from 2003 to 2017. This study implies a Hausman test to identify which particular tests are more suitable and selected a fixed effect test and granger causality test for effective analysis perspective. Moreover, this study further relies on the panel vector error correcti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 99 publications
5
17
0
Order By: Relevance
“…Renewable energy with pollution and mortality is well explored in literature. Numerous studies suggested that RE consumptions provide a clean environment with fewer emissions of dangerous gases, i.e., CO 2 , SO 2 , and NO 2 (36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47). Indeed, fossil fuels are the key source of greenhouse emissions and other air pollutants having a negative connection with human health, and these lead to respiratory and cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Renewable energy with pollution and mortality is well explored in literature. Numerous studies suggested that RE consumptions provide a clean environment with fewer emissions of dangerous gases, i.e., CO 2 , SO 2 , and NO 2 (36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47). Indeed, fossil fuels are the key source of greenhouse emissions and other air pollutants having a negative connection with human health, and these lead to respiratory and cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, various economists (including Bajpai and Sachs, 2000, p. 1) advised policymakers in India to adopt the open-door policy to FDI which is believed to bring plenty of benefits such as knowledge, new technology and a tremendous amount of capital inflows (Balasubramanyam et al ., 1996). These benefits of FDI positively affect economic growth (De Mello, 1997); and lots of studies (Anser et al , 2021a, b; Suliman and Elian, 2014; Temiz and Gokmen, 2014; Dash and Parida, 2013; Jayachandran and Seilan, 2010; Li and Liu, 2005; Blomströom and Kokko, 1996) have discussed the relationship between FDI and economic growth. Similarly, Balasubramanyam et al (1996) propose that support to the FDI is a more significant determinant for the economic growth of any country because it is encouraging to the exports, and resultantly imports also get promoted.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown a positive, negative and insignificant relationship between FDI inflows and economic growth (see Adewumi, 2007; Li and Liu, 2005; Khuong et al , 2021; Jayachandran and Seilan, 2010; Li et al , 2021; Anser et al , 2021a, b; Temiz and Gokmen, 2014). The majority of studies used a cointegration method to investigate the long-term relationship between FDI inflows and economic growth (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…GFCF and business regulation increase FD Mohsin et al ( 2021 ) RE, non-RE, EG, GHG, Management Policy, POP Asian economies Random effect EG ↔ RE Doytch & Narayan ( 2021 ) RE, non-RE, EG, FDI, government stability, manufacturing and service growth Middle-, low-, and High-income countries Panel regression RE and Non-RE improve EG in all countries Salari et al ( 2021 ) RE, residential energy consumption, EG, household size, gas tax USA GMM RE drive EG. Confirming the growth hypothesis for the United States Anser et al ( 2021 ) EG, solar, wind, geothermal, biomass and hydropower energy South Asia PVECM; DOLS Various types of RE (solar, wind, geothermal, and hydropower) propel EG in South Asian economies Ivanovski et al ( 2021 ) RE, EG, non-RE, GFCF, labour force OECD and non-OECD Dynamic-CCEMG RE, non-RE, and GFCF increase EG for the full sample Baz et al ( 2021 ) RE, EG, fossil fuel, labour, FDI, capital Pakistan Non-linear ARDL EG ↔ fossil fuel FDI → EG Zhe et al ( 2021 ) FD, RE, EG, Turkey VAR Model RE and FD have no significant influence on EG. However, RE significantly influences FD Khan et al ( 2021 ) EG, energy trilemma, non-Re, FD, POP Top ten countries in WATI FMOLS; GMM Non-RE and FD increase EG Shahbaz et al ( 2021 ) ...…”
Section: Brief Empirical Reviewmentioning
confidence: 78%